Treatment of Tinea pedis outpatientes with Miconazole - Barros, J. Martins de; Belda, Walter (Revista de Saúde Pública, 1972)
Twenty six patients of Tinea pedis were treated with Miconazole 2-3 times a day. The drug was used as lotion, cream or powder in local applications. Lesions ameliorated or disappeared in 23 patients (88%), within an average period of 2-4 weeks.